Exploring the Effects of Information and Communication Technology as a Pedagogy for Teaching Business Studies in Grade 10 in the Lejweleputswa Education District, South Africa - Masilo Pule David Mashabe; Motalenyane Alfred Modise (E-Journal of Humanities, Arts and Social Sciences)
This research explored the effect of Information and Communication Technology as a pedagogy for teaching Business Studies in Grade 10. The participants were educators from three high schools in the Lejweleputswa Education District, from the Free State province, South Africa. However, they revealed that the adoption of ICT needs diverse development in terms of curriculum, educators’ training and development, assessment strategies, educators’ competence and various forms of teaching strategies. Thematic analysis revealed that ICT has a great and positive effect as a pedagogy because educators will be able to explain and transmit content knowledge to learners to meet the curriculum goals and objectives. This research recommends that, in order to declare the use of ICT as a pedagogy for teaching Grade 10 Business Studies in Lejweleputswa Education District. Educators need to be competent. Training and development need to be done as a commitment to advance learners with skills set for being future business people. The seeks to offer strategies for the Department of Basic Education (DBE) at the provincial, regional and district levels to be consistent and effective in supplying ICT apparatus across the province to ensure quality of education and sufficient transfer of skills. It should be acknowledged that the goal of ICT in schools is to inculcate learners with technological skills in order to mend and respond to the requirements of the Fourth Industrial Revolution (4IR) as well as Artificial Intelligence (AI).